Kepemimpinan Kepala Sekolah dalam Pengembangan Tingkat Resiliensi - Handika Yuda Saputra; Dian Hidayati (Journal of Education and Teaching (JET), 2024)
This research is motivated by the unfavourable conditions of a school, ranging from the quantity of students to the salaries of teachers and staff, forcing school leaders to employ resilient measures for the school's sustainability. The aim of this study is to analyse and provide a detailed description of the school principal's leadership in setting the direction, developing people, and redesigning the organization to enhance the school's resilience. The research adopts a qualitative approach utilizing data collection techniques such as observation, interviews, and documentation, with data analysis techniques involving description, analysis, and interpretation. The findings of this research explain that by fulfilling these three leadership roles—Setting the Direction, Developing People, and Redesigning Organization—a private school can effectively enhance its resilience.